Effects of anxiety and depression and early detection and management of emotional distress on length of stay in hospital in non-psychiatric inpatients in China: a hospital-based cohort study. Issue 1 (October 2019) - Guo, Wan-Jun; Wang, Hui-Yao; Deng, Wei; Huang, Ming-Jin; Dong, Zai-Quan; Liu, Yang; Luo, Shan-Xia; Yu, Jian-Ying; Huang, Xia; Chen, Yue-Zhu; Shen, Chun-Tao; Ren, Tian-Rui; et al.
Abstract: Background: Emotional distress, including anxiety and depression, is associated with negative outcomes (such as poorer prognosis of physical diseases, longer hospital stays, and more readmissions) of patients in non-psychiatric settings. We investigated the effects of anxiety and depression, as well as the effects of early detection and management of emotional distress, in non-psychiatric inpatients on length of stay in hospital, with the aim of better informing the provision of medical care to meet the needs of non-psychiatric patients receiving general hospital care. Methods: This real-world hospital-based cohort study included inpatients (aged ≥15 years) from 20 non-psychiatric departments in West China Hospital. The Huaxi emotional-distress index (HEI), a validated questionnaire for screening depression and anxiety in Chinese non-psychiatric clinical settings, was recommended for use in brief screening of non-psychiatric inpatients on their admission to hospital. Patients with depression or anxiety were provided with a graded psychological service, ranging from brief supportive care (for mild distress [HEI score 9–12]) to treatment by a psychiatrist or psychotherapist (for severe distress [HEI score ≥17]). Patients were grouped on the basis of whether brief screening and graded psychological service was provided (BS-GPS group) or not (non-BS-GPS group). Length of stay was compared between the groups and between patients with and without clinically significant anxiety or depression. Findings: From Jan 1, 2015, to Dec 31, 2018, 487 871 patients admitted to 20 non-psychiatric departments were included in the study, of whom 178 883 (36·7%) patients underwent brief screening on admission (BS-GPS group) and 308 988 (63·3%) patients were not screened (non-BS-GPS group). Across all departments, 9590 (5·4%) patients in the BS-GPS group (range 2·6–20·5% across departments) showed clinically significant anxiety or depression (ie, total HEI score ≥11). Mean length of stay differed significantly between patients with (12·7 days [SD 0·12]) and without (9·5 days [0·02], p<0·0001) clinically significant anxiety or depression, and between the BS-GPS group (9·6 days [0·02]) and the non-BS-GPS group (10·8 days [0·02], p<0·0001). These differences remained significant after controlling for sociodemographic factors and categories of physical diseases. Interpretation: Anxiety and depression significantly prolonged the length of stay of non-psychiatric inpatients in general hospital. Early detection and management of emotional distress should be promoted and applied to better care for patients with non-psychiatric disorders and to conserve medical resources. Funding: 1.3.5 Project for Disciplines of Excellence of West China Hospital (Sichuan University), Science and Technology Benefit the People Project of Chengdu Municipal Government (grant numbers 2015-HM01-00011-SF and 2016-HM02-00095-SF ), Science and Technology Support Program of Sichuan Provincial Government (grant number 2015SZ0058 ).